Efficient fracture mechanics programming system for linear and non-linear problems using finite-element and boundary-element methods - Al-Edani, Ameen Ahmed Nassar (Cranfield University, 1990)
An attempt has been made, in this work, to design an efficient, linear—elastic and elasto-plastic, fracture mechanics package based upon finite and boundary element methods. The package contains many useful facilities such as, pre- and post-processors, different types of loading including inertial and thermal loading, and different types of finite and boundary elements. New crack-tip elements, and efficient algorithms for the analysis of J-integrals, have been derived. Elasto-plastic boundary element programs with different types of loading, and using a new subregion facility have also been developed. The package was employed for fracture mechanics analysis of some case studies with elastic, thermo-elastic, and elasto-plastic conditions, and with one and two modes of fracture. The results have proved that the package is very reliable and controllable, and new facilities and techniques, developed in this work, can provide useful tools for fracture mechanics analysis.